Pengaruh krisis moneter terhadap pola dan tingkat konsumsi petani karet - M. Basir Kimin (Universitas Islam Indonesia, 2001)
The monetary crisis reflected in low change rate of rupiah towards US dollars which is eventually followed by the raising of prices gives effect to disposable and real income rate pattern and level of people's consumption.